Link between the causative genes of holoprosencephaly: Zic2 directly regulates Tgif1 expression - Ishiguro, Akira (Sci Rep, 2018)
One of the causal genes for holoprosencephaly (HPE) is ZIC2 (HPE5). It belongs to the zinc finger protein of the cerebellum (Zic) family of genes that share a C2H2-type zinc finger domain, similar to the GLI family of genes. In order to clarify the role of Zic2 in gene regulation, we searched for its direct target genes using chromatin immunoprecipitation (ChIP). We identified TGIF1 (HPE4), another holoprosencephaly-causative gene in humans. We identified Zic2-binding sites (ZBS) on the 5′ flanking region of Tgif1 by in vitro DNA binding assays. ZBS were essential for Zic2-dependent transcriptional activation in reporter gene assays. Zic2 showed a higher affinity to ZBS than GLI-binding sequences. Zic2-binding to the cis-regulatory element near the Tgif1 promoter may be involved in the mechanism underlying forebrain development and incidences of HPE.